Idea komplementarności ekspertymentów - Sobczyńska, Danuta (Filozofia Nauki, 1996)
J. Such first introduced the notion of „complementary experiments”, referring to the decisive situations in science. The similar notions appears in the discussions of new experimentalists. For example, I. Hacking writes about complementarity of different types of microscopy, A. Franklin distinguishes technically good and conceptually important experiments, and P. Galison analyses examples of complementarity of two different approaches to the problem of cosmic radiation. In the article the notion of „complementarity” is extended as to cover the cases of complementarity of method, complementarity of scientific teams etc. As an illustration it is used the case of discovering new type of carbon - called „fulleren”.